2021
DOI: 10.1177/23337214211058919
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the COVID-19 Pandemic for Dementia Research: Engaging Rural, Older, Racially and Ethnically Diverse Church Attendees in Remote Recruitment, Intervention and Assessment

Abstract: Background Access to cognitive screening in rural underserved communities is limited and was further diminished during the COVID-19 pandemic. We examined whether a telephone-based cognitive screening intervention would be effective in increasing ADRD knowledge, detecting the need for further cognitive evaluation, and making and tracking the results of referrals. Method Using a dependent t-test design, older, largely African American and Afro-Caribbean participants completed a brief educational intervention, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…We highlight these critical tenants of ADRD rural research and encourage their incorporation in all research moving forward: Local faith-based leaders should be asked to identify congregation members as potential research assistants, which has been shown to be effective in increasing levels of ADRD knowledge, screening, diagnosis rates, 228 and care management after diagnosis in rural areas. 229 The collaboration of community members ensures buyin and support for culturally responsive education programs and interventions to reduce ADRD-related health disparities in rural communities.…”
Section: A Call To Actionmentioning
confidence: 99%
See 4 more Smart Citations
“…We highlight these critical tenants of ADRD rural research and encourage their incorporation in all research moving forward: Local faith-based leaders should be asked to identify congregation members as potential research assistants, which has been shown to be effective in increasing levels of ADRD knowledge, screening, diagnosis rates, 228 and care management after diagnosis in rural areas. 229 The collaboration of community members ensures buyin and support for culturally responsive education programs and interventions to reduce ADRD-related health disparities in rural communities.…”
Section: A Call To Actionmentioning
confidence: 99%
“…Subsequently, specialist telehealth clinics can support local primary care services to enhance detection and diagnosis 135 . Providing culturally tailored, cost‐effective, and simple solutions for ADRD diagnosis and management is an important step for capacity building in LMICs, indigenous peoples, and other rural populations 228 . Developing, adapting, and validating cognitive assessment tools informed by local values is underway at an international level 229 .…”
Section: The Future Of Adrd Research In Rural Areasmentioning
confidence: 99%
See 3 more Smart Citations